TRANSFER OF A BUSINESS SHARE IN A LIMITED LIABILITY COMPANY WHEN TRANSFERRING TO THE NEXT GENERATION (Collected Papers of the Law Faculty of the University of Rijeka, 2025)
Membership changes in companies can be complex and challenging for various reasons. The majority of members of a limited liability company, who are often (but not necessarily) members of the management  board, may entrust the management of the  company’s affairs to others upon retirement. They then face the question of what to do with their  business shares. In the case of a family company, the  founder must decide whether to gift or sell the  shares to younger family members or other individuals. Sometimes, the issue of intergenerational succession of management and membership  functions in the company arises unexpectedly  through inheritance of a business share. The goal of this article is to analyze the challenges of legally structuring the transfer of a business share in a limited liability company through a gift contract to selected family members. It will address  controversies that may arise and answer common questions in corporate and judicial practice regarding inheriting a business share. Additionally, the paper will suggest ways to legally prevent the identified  challenges.